Kumpulan pahlawan Indonesia terlengkap - Mirnawati (Mekarsari, Cimanggis, Depok : CIF, 2012)
Biographical sketches of Indonesian heroes.
Daftar pustaka : p. 306.
Keywords: Heroes -- Indonesia -- Biography; Nationalists -- Indonesia -- Biography; Indonesia -- Biography